2015
DOI: 10.1002/app.43022
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 0.4Li2MnO3·0.6LiNi1/3Co1/3Mn1/3O2 with tunable morphologies via polyacrylonitrile as a template and applications in lithium‐ion batteries

Abstract: Samples of 0.4Li 2 MnO 3 Á0.6LiNi 1/3 Co 1/3 Mn 1/3 O 2 (LMO) with tunable morphologies were synthesized via polyacrylonitrile (PAN) as a template. The starting PAN/N,N-dimethylformamide (DMF) ratios, including 1:9, 1:10, 1:12, and 1:14, were optimized for the fiber morphologies and electrochemical performance. Through electrospinning, metal salts were well dispersed in the PAN fibers. The crystal structure and morphologies of the PAN/LMO fibers were characterized by X-ray diffraction, scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The pie chart clearly shows that ES-LLO has one of the highest capacities of all the studies reported. Few similar or slightly higher capacity results are reported in the literature (see refs ,, for the pie chart given in the Supporting Information section); however, it is worth noting that the Co content in our data is the lowest compared to all the reported work on the fibrous compound. Reference which highlights the highest capacity of 300 mA hg –1 is the value measured at 0.05 C-rate.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The pie chart clearly shows that ES-LLO has one of the highest capacities of all the studies reported. Few similar or slightly higher capacity results are reported in the literature (see refs ,, for the pie chart given in the Supporting Information section); however, it is worth noting that the Co content in our data is the lowest compared to all the reported work on the fibrous compound. Reference which highlights the highest capacity of 300 mA hg –1 is the value measured at 0.05 C-rate.…”
Section: Resultssupporting
confidence: 85%
“…Cathodes form an important active material in LIBs. Energy and power density of the cathode materials are critical parameters for ascertaining the electrochemical performance of the LIB for specific application. , Currently, commercial LIBs are made using layered LiCoO 2 -type cathodes because of stable initial specific capacity (140 mA h g –1 ) and stable electrochemical cycling. However, because of the high cost and toxicity, these conventional cathode materials cannot be extended to large-scale applications including electric vehicles. , Furthermore, batteries operating at high charging–discharging rates are required for wider commercialization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned that this electrospinning technology is not well-suited to prepare very long nanofibers in the range of several millimeters, as it is possible with the needle-based process [39][40][41]. Due to the usually isotropic arrangement and the interconnections formed between the fibers, length estimation of fibers spun by a wire-based technology is difficult and, to the best of our knowledge, not yet reported in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…While there are few studies that address the methods to improve the electrochemical properties of cathode materials, such as Li-rich layered oxide, studies on nanofibrous Ni-rich layered oxides processed by the ES technique are scarce. 15,16 In this manuscript, we explore enhancing the cyclic performance of nanofibrous Ni-rich layered oxide cathodes by optimizing the process parameters during synthesis and the annealing condition. ES of polymer solution is a novel and efficient technique to prepare 1D solid, hollow, and porous NFs.…”
Section: Introductionmentioning
confidence: 99%